Practices and Beliefs at Pharmacy Students - Jiménez, Luis Guillermo (2024)
Well-being of students is related to a set of determinants. Objective to evaluate opinion of healthy practices and beliefs of pharmacy students at the University of Costa Rica. This is a descriptive and cross-sectional study in which students were invited to answer a questionnaire about healthy practices. 106 students participated, the majority with a favorable general perception of health, specially towards leisure time - recreation, job security and eating habits, but unfavorably in physical activity and sports, consumption of psychoactive substances - others and sleep; beliefs are generally oriented towards health promotion. Pharmacy students generally have favorable beliefs towards health with reduced practice due to conditions that limit developing activities in accordance with beliefs. Must opportunities be necessary to generate students’ well-being at the academic environment.Keywords: education, perception, health.